Integrated Qs Al Mudatsir in the reality group counseling to grow the character of students academic responsibility - Asroful Kadafi; M. Ramli (Universitas PGRI Madiun, 2017)
AbstractThe emotional development of students in early teens showed a sensitive and recreative nature (critical), emotions are often negative and temperamental. This negative passion is evidenced by the findings in the field of Indonesian teenagers, such as Tawuran, promiscuity, students who dare to do nasty with school friends (Tirto, 2013). Many factors are the cause, one of which is still the weak character of academic responsibility that students have. This problem becomes a serious problem in the world of education Indonesia. Therefore, it is natural for educational practitioners to take solutive steps to overcome the problem. One education practitioner who has a strategic position to handle the case is Counselor. Counselors are deemed able to provide practical solutions through Reality Group Counseling services by integrating spiritual values (Islam) to foster student academic responsibilities. Reality group counseling emphasizes the growth of personal responsibility. This advice is also in line with Islamic values that encourage individuals always to be responsible for every action as reflected in the QS. Al Muddassir: 38).